Pengaruh Gaya Kepemimpinan dan Komitmen Organisasi terhadap Kinerja Karyawan PT Sintesa Biru Utama Bogor - Faiz Dian Nugroho; Imam Muhtadin (Masyarakat Ekonomi Syariah Bogor, 2026)
The decline in employee performance at PT Sintesa Biru Utama from 85% (2023) to 79% (2024) requires The decline in employee performance at PT Sintesa Biru Utama from 85% (2023) to 79% (2024) requires an evaluation of leadership style and organizational commitment. This study aims to analyze the influence of leadership style and organizational commitment on employee performance at PT Sintesa Biru Utama Bogor. This study uses an associative quantitative approach with data obtained through questionnaires to 52 respondents who are employees of PT Sintesa Biru Utama Bogor. The results show that leadership style does not have a positive and significant effect on employee performance (t = 1.939 < 2.01; sig = 0.058 > 0.05). Meanwhile, organizational commitment has a positive and significant effect on employee performance (t = 4.924 > 2.01: sig = 0.001 < 0.05). However, simultaneously, both have a positive and significant effect on employee performance (f = 41.795 > 3.19: sig = 0.001 < 0.05). The R Square value of 0.630 indicates that both variables explain 63% of the variation in employee performance. These results confirm organizational commitment as a major factor in the performance of employees at PT Sintesa Biru Utama Bogor.